Recent advances in constraints 14th annual ERCIM international workshop on constraint solving and constraint logic programming, CSCLP 2009, Barcelona, Spain, June 15-17, 2009 : revised selected papers - Joint ERCIM/CoLogNet International Workshop on Constraint Solving and Constraint Logic Programming 2009 Barcelona, Spain); Larrosa, Javier; O'Sullivan, B. (Barry).; SpringerLink (Online service). (Berlin New York Springer, 2011)
This book constitutes the thoroughly refereed post-proceedings of the 14th Annual ERCIM International Workshop on Constraint Solving and Constraint Logic Programming, CSCLP 2009, held in Barcelona, Spain, in June 2009. The 9 revised full papers presented were carefully reviewed and selected for inclusion in this post-proceedings. The papers in this volume present original research results and applications of constraint solving and constraint logic programming in several domains. Among the issues addressed are solving argumentation frameworks, software consistency, modeling languages, static design routing, dynamic constraint satisfaction, and constraint-based modeling.
Solving Weighted Argumentation Frameworks with Soft Constraints -- Connecting BnB-ADOPT with Soft Arc Consistency: Initial Results -- Procedural Code Generation vs Static Expansion in Modelling Languages for Constraint Programming -- Solving the Static Design Routing and Wavelength Assignment Problem -- A Resource Cost Aware Cumulative -- Integrating Strong Local Consistencies into Constraint Solvers -- Dynamic Constraint Satisfaction Problems: Relations among Search Strategies, Solution Sets and Algorithm Performance -- Constraint-Based Modeling and Scheduling of Clinical Pathways -- MAC-DBT Revisited.
Electronic reproduction.
Keywords: Constraints (Artificial intelligence) -- Congresses; Constraint programming (Computer science) -- Congresses; Electronic books